Development dramas : reimagining rural political action in Eastern India - Da Costa, Dia. (New Delhi ; New York : Routledge, 2010)
Study with reference to Jana Sanskriti Centre for Theatre of the Oppressed, Calcutta, India.
Includes bibliographical references (p. [270]-291) and index.
Keywords: India -- Politics and government -- 21st century